A Similitude Design Method of Rotating Thin-wall Short Cylindrical Shell Considering Nonlinear Vibration Response - Luo, Zhong; Zhu, Yunpeng; Wang, You; Wang, Fei; Han, Qingkai (Journal of Vibration Testing and System Dynamics, 2026)
This study investigates the non-linear dynamic scaling laws for a rotating thin-wall short cylindrical shell. By introducing the geometric non-linear term, corresponding governing equations are employed to establish the non-linear scaling laws. Both the natural frequency and single-point excitation response of the rotating cylindrical shell are investigated. The applicability of the scaling laws of the rotating thin-wall short cylindrical shell is veriﬁed numerically. In addition, the scaling laws for linear and non-linear vibrations are compared. Analytical results indicate that the scaled model designed by the non-linear scaling laws are more restrictive than that of using the linear scaling laws. In addition, they predict the characteristics of the prototype with good accuracy.